Powerplays how teens can pull the plug on sexual harassment - Hodgson, Harriet W. (Deaconess Press, 1993)
Explains how teenagers can identify, fight, and prevent sexual harassment in school and on their jobs, stressing how inaction may sometimes lead to sexual abuse.